Crystal structure and magnetic properties of two salts of nickel-bis-1, 2-dithiolene with ammonium organic cation. (15th January 2019) - Chen, Xuan-Rong; Hu, Wei-Yang; Xu, Xiao-Yi; Ren, Fang-Fang
Graphical abstract: Two nickel-bis-1, 2-dithiolene molecular solids, [( n -Bu)Et3 N][Ni(mnt)2 ] (1 ) and [( n -Bu)Et3 N][Ni(dmit)2 ] (2 ), were synthesized and characterized by IR spectra, thermal analysis and single crystal structures. The variable-temperature susceptibility analysis shows that1 shows simple Curie–Weiss type paramagnetic behavior, and2 exhibits a magnetic phase transition around 22 K with a ca. 2 K hysteresis loop. Abstract: Two nickel-bis-1, 2-dithiolene salts, [( n -Bu)Et3 N][Ni(mnt)2 ] (1 ) and [( n -Bu)Et3 N][Ni(dmit)2 ] (2 ) (mnt 2−  = maleonitriledithiolate, dmit 2−  = 4, 5-di(thiobenzoyl)-1, 3-dithiole-2-thione), ( n -Bu)Et3 N +  = triethylbutylammonium), were synthesized and characterized by IR spectra, thermal analysis and single crystal structures. The two salts crystallize in monoclinic space group C2/c and P2(1)/n with a formula and cell parameters of C18 H24 N5 NiS4, a  = 29.109(3) Å, b  = 7.7083(9) Å, c  = 22.318(3) Å and β  = 108.885(3)° for1 at 293 K versus C16 H24 NNiS10, a  = 8.1501(15) Å, b  = 27.239(5) Å, c  = 12.064(2) Å and β  = 103.354(6)° for2 at 293 K. Moreover, the two salts show similar packing structure, and the anions and cations in1 are aligned into columnar stacks along b -axis direction; the anions and cations in2 are aligned into separated columnar stacks along a -axis direction. Temperature dependence of magnetic susceptibility demonstrates that the simple Curie–Weiss type paramagnetic behavior was observed in salt1 and a magnetic phase transition appears around 22 K with a ca. 2 K hysteresis loop for2, and the magnetic data was well fitted through Curie–Weiss type model and 1-D linear chain model.